1st cosmetic workshop: cosmetic formulation / Muhammad ‘Izzuddin Zamery - Zamery, Muhammad ‘Izzuddin (Faculty of Pharmacy, 2024)
he 1st Cosmetic Workshop on Cosmetic Formulation was enthusiastically organised by the Faculty of Pharmacy, Universiti Teknologi MARA (UiTM) Puncak Alam Campus on June 13 and 14, 2024. The Department of Pharmaceutical Technology hosted this ground-breaking event with the goal of providing faculty and staff with the information and hands-on training needed to develop and produce cosmetic products, particularly detergent and soap. Twenty faculty members from different departments eagerly participated in the session, which was led by Adjunct Professor Dr. Tommy Julianto Bustami Effendi. Famous for his vast experience and expertise in the industry, Dr. Tommy offered valuable insights into the fundamental knowledge of cosmetic ingredients, their functions and recommended compositions.